2011
DOI: 10.1051/0004-6361/201015875
|View full text |Cite
|
Sign up to set email alerts
|

WASP-33: the firstδScuti exoplanet host star

Abstract: We report the discovery of photometric oscillations in the host star of the exoplanet WASP-33 b (HD 15082). The data were obtained in the R band in both transit and out-of-transit phases from the 0.3-m telescope and the Montcabrer Observatory and the 0.8-m telescope at the Montsec Astronomical Observatory. Proper fitting and subsequent removal of the transit signal reveals stellar photometric variations with a semi-amplitude of about 1 mmag. The detailed analysis of the periodogram yields a structure of signif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
100
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(116 citation statements)
references
References 23 publications
13
100
3
Order By: Relevance
“…Our measured inclination matches well with previous studies (Collier Cameron et al 2010;Herrero et al 2011;Smith et al 2011;Kovács et al 2013;von Essen et al 2014), but the planetary radius is found to be up to 3σ larger. This highlights the fact that WASP33b is substantially bloated in comparison to other exoplanets.…”
Section: E X a M P L E S C I E N C Esupporting
confidence: 92%
See 1 more Smart Citation
“…Our measured inclination matches well with previous studies (Collier Cameron et al 2010;Herrero et al 2011;Smith et al 2011;Kovács et al 2013;von Essen et al 2014), but the planetary radius is found to be up to 3σ larger. This highlights the fact that WASP33b is substantially bloated in comparison to other exoplanets.…”
Section: E X a M P L E S C I E N C Esupporting
confidence: 92%
“…The planet is also observed to be hotter and more bloated than most other exoplanets. In addition, there have been tentative claims of a resonance between the period of orbit and period of pulsations, suggesting a tidal link (Herrero et al 2011).…”
Section: E X a M P L E S C I E N C Ementioning
confidence: 99%
“…Herrero et al 2011). It was discovered within the transit survey of the WASP project by Christian et al (2006) to show planet-like transits with a period of 1.22 d. WASP-33b, the first short-period planet of an A-type star, was finally confirmed by Collier Cameron et al (2010, CC10 hereafter).…”
Section: Introductionmentioning
confidence: 94%
“…It is the first planet discovered to orbit an A-type star (Herrero et al 2011). This system has been extensively studied with photometry and spectroscopy (Herrero et al 2011;Moya et al 2011;Smith et al 2011;Deming et al 2012;Sada et al 2012;de Mooij et al 2013;von Essen et al 2014;Hardy et al 2015;Haynes et al 2015;Johnson et al 2015;von Essen et al 2015).…”
Section: Wasp-33bmentioning
confidence: 99%